Influence of ancient glacial periods on the Andean fauna: the case of the pampas cat (Leopardus colocolo) - Cossíos, Daniel (2009)
Background: While numerous studies revealed the major role of environmental changes of the Quaternary on the evolution of biodiversity, research on the influence of that period on current South-American fauna is scarce and have usually focused on lowland regions. In this study, the genetic structure of the pampas cat (Leopardus colocolo), a widely distributed felid, was determined and linked to ancient climate fluctuations on the Andean region. Results: Using both mitochondrial sequences and nuclear microsatellites, we inferred the existence of at least four groups of populations in the central Andes, while other three localities, with little sample sizes (n = 3), presented differences in only one of these markers. The distribution of these groups is correlated to latitude, with a central area characterized by admixture of numerous mitochondrial clades. This suggests colonization from at least three glacial refuges and a contact zone between 20 degrees and 23 degrees S following a glaciation event. The similar coalescence times of the mitochondrial haplotypes indicated that the major clades split approximately one million years ago, likely during the Pre-Pastonian glacial period (0.80 – 1.30 MYA), followed by a demographic expansion in every clade during the Aftonian interglacial period (0.45 – 0.62 MYA). Interestingly, this structure roughly corresponds to the current recognised distribution of morphological subspecies. Conclusion: The four groups of populations identified here must be considered different management units, and we propose the three localities showing differences in only mtDNA or ncDNA as provisional management units. The results revealed the influence of ancient climate fluctuations on the evolutionary history of this species. It is expected that the other species of land vertebrates with a smaller or similar mobility have been affected in the same manner by the glacial and interglacial periods in the central Andes.